HUBUNGAN GAYA HIDUP DAN DUKUNGAN KELUARGA DENGAN PENGENDALIAN HIPERTENSI PADA LANSIA DI WILAYAH KERJA PUSKESMAS SUKAMAJU BARU TAHUN 2020 - Annice Luthfiya Rochani (2021)
Most of the elderly are suffering from non-communicable disease, especially hypertension. Riskesdas 2018 showed that the prevalence of hypertension at the age of 65 - 74 years is 63.2%. And also, there is 1.227 elderly with hypertension in Puskesmas Sukamaju Baru area 2019. To prevent complication, they need a good hypertension management behavior. One of the ways to control the hypertension is by maintaining a healthy life style, especially eat, sleep, and physical activity habits. Besides life style, they also need a good family support to help the elderly in controlling their hypertension. The aim of this research is to know the correlation between life style and family support with hypertension control behavior in elderly. This research used quantitative method with cross-sectional approach. This research was conducted in November 2020 - January 2021 at Sukamaju Baru Primary Health Care area with a total sample of 293 people. The sampling technique was cluster random sampling. The results of the chi square statistical tests showed that there were a correlation between life style (eat, sleep, and physical activity habits) and family support (assessment, instrumental, informational, and emotional support) with hypertension control behavior in elderly (p < 0,05). It hopes this research data could become the basis of the intervention that will be held by the primary health care, and also the suggestion for the families are to increase their support for the elderly to be able to implement a good hypertension control behavior in their daily lives. Keywords: Family Support, Life Style, Hypertension